Phenolic content and antioxidant activity of young and mature mango (Mangifera indica) and avocado (Persea americana) leave extracts - Félicité Kingne Kingne; Fabrice Tonfack Djikeng; Hermine Doungue Tsafack; Mallampalli Sri Lakshmi Karuna; Hilaire Macaire Womeni (International Journal of Phytomedicine, 2018)
Polyphenols are groups of secondary metabolites in plants, known with their various biological activities, including their ability to act as antioxidants. Due to the side effects of the use of synthetic antioxidants on human’s health, the search for natural less toxic compounds has significantly increased. This study was carried out to evaluate the phenolic content and antioxidant activity of young and mature avocado (Persea americana) and mango leaves (Mangifera indica). Different extracts were prepared by maceration in methanol, ethanol, cold and hot water. The phenolic content of the extracts was determined using the Folic-Ciocalteu Method. A total of three antioxidant tests were done on the extracts: the 2, 2-diphenyl-1-picrylhydrazyl test (DPPH test), the Ferric reducing antioxidant power and the Hydroxyl radical scavenging activity. Results of these investigations generally showed that the mature leaves of mango and young leaves of avocado exhibited the highest phenolic and flavonoid contents, as well as the antioxidant activity. They can be recommended as good sources of antioxidants to reduce the damages caused by free radicals and reactive oxygenated species in the body. They can also be recommended as a source of antioxidants for the preservation of oils, food containing lipids and pharmaceutical products.